PREDIKTOR KEPUTUSAN PEMBELIAN RAMAH LINGKUNGAN (KASUS WISATAWAN PENGGUNA HOTEL RAMAH LINGKUNGAN DI YOGYAKARTA) - Nining Yuniati (Universitas Merdeka Malang, 2019)
A number of studies have addressed the predictors that influence green purchasing, but none have specifically provided confirmation of which predictors are most influential. This study was conducted to determine the effective contribution and relative contribution of the predictors that influence the purchasing decision of environmentally friendly hotels. An incendetal survey was carried out on 87 tourists who stayed in environmentally friendly hotels, the result were statistically tested. Five predictors that are considered to influence green purchasing decisions are green experiences, environmental concern, hotel image, price, and reference groups. Effectively the five predictors contribute 84% to green purchases. Relatively all predictors have a contribution of up to 100% meaning that all five are correct predictors. Environmentally concern is the most influential predictor in green purchasing decisions. Overall, all predictors are strategies for green hotel businesses to increase the number of guests, in terms of green experience, environmentally concern, price, image, and reference groups.